Integrated dry NO sub x /SO sub 2 emissions control system - United States. Department of Energy. (Public Service Co. of Colorado, Denver, CO (United States), 1991)
A per the DOE Cooperative Agreement No. DE-FC22-91PC90550 dated March 11, 1991, Public Service Company of Colorado has prepared the following quarterly report for Phase I, IIA, and IIB of the Integrated Dry NOsub x/SOsub 2 Emissions Control System Project. This project includes Low NOsub x Burners with post firing air injection, humidification, and dry sorbent injection. This quarterly report covers the quarterly period April, May, and June, 1991. This report covers project activities for the second three months period of the project.